The Relationship between the Knowledge of the Prospective Bride (catin) and the Prevention of HIV/AIDS Transmission - Sri Lestari; Yulia Irvani Dewi; Ade Dilaruri (Journal of Education Technology Information Social Sciences and Health, 2024)
Until now, Indonesia is still facing cases of HIV/AIDS. One of the causes of the high number of HIV/AIDS cases is the lack of public knowledge about HIV/AIDS. This research aims to determine the relationship between the prospective bride and groom's knowledge (catin) and the prevention of HIV/AIDS transmission. This research uses a descriptive correlation design and a cross sectional approach. The research sample was 100 respondents taken based on inclusion criteria using simple random sampling techniques. The analysis used in this research was the chi-square test. The research results showed that 55 (55%) respondents had high knowledge about HIV/AIDS and prevention, 38 (38%). The results of statistical tests show that there is no relationship between knowledge and prevention of HIV/AIDS transmission in prospective brides and grooms with p value (0.320) alpha (0.05). There is no relationship between the bride and groom's knowledge and prevention of HIV/AIDS transmission.